(untitled) (Biuletyn Kryminologiczny, 2013)
In recent years there have been an increasing number of cases of dissemination of intimate images or videos without the consent of the victim, even though there was previous agreement to the recording. The typical example of this is when a person consents to be recorded while maintaining a sexual relationship or any other intimate act of their life (taking a shower, changing clothes or undressing during an internet communication), which are subsequently published on websites (social networks, forums, pornographic websites, etc.) without their authorization. Commonly these images are released by spite or revenge of an ex- partner after the breakup of the relationship, used as blackmail or a simple joke by a friend.